Impact of Artificial Intelligence on Learning Outcomes: A Study in the Context of Bangladesh (The Science Post, 2025)
This study examines the transformative potential of Artificial Intelligence (AI) in shaping learning outcomes withinBangladesh’ s evolving educational landscape. Leveraging a mixed-methods approach that integrates large-scalesurveys, in-depth interviews, and secondary data analysis, the research explores how AI-driven tools—ranging fromintelligent tutoring systems to adaptive learning platforms — impact student performance, engagement, andpersonalized instruction across K–12 and higher education sectors. Findings reveal that AI can significantly enhanceacademic achievement, foster individualized learning experiences, and improve teaching efficiency when supportedby robust infrastructure, teacher readiness, and localized digital content in Bangla. However, challenges such aslimited technological capacity in rural regions, unequal access to digital resources, and concerns around data privacy,algorithmic bias, and ethical governance constrain large-scale adoption. The study highlights strategic pathways forintegrating AI responsibly and sustainably, offering policy recommendations for government agencies, educationalinstitutions, and EdTech developers. These include capacity-building initiatives, inclusive digital infrastructuredevelopment, and regulatory frameworks that ensure equity, cultural alignment, and data security. Ultimately, theresearch underscores AI ’ s potential to drive inclusive educational innovation in Bangladesh while addressingsystemic barriers to its effective implementation.